Dialectics Between Suspicion and Trust - Brassier, Ray (Stasis, 2016)
Suspicion toward reason is integral to much contemporary critical theory. The proximate source for this spirit of suspicion is undoubtedly Nietzsche’s genealogical unmasking of the will to truth as will to power. Robert Brandom summarizes this development as follows: Where the Enlightenment disenchanted the world through reason, genealogy is disillusionment with reason. Genealogy is the skeptical exacerbation of critique, the point at which it becomes suspicious of its own residual rationalism. The move from critique to genealogy marks the shift from the rational demarcation of reason’s limits to the skeptical destitution of reason’s authority. But reason is dialectical precisely to the extent that disenchantment presupposes an underlying trust in the capacities of conceptual rationality. Without such trust, the absolutization of genealogical suspicion lapses into metaphysical credulity toward an ultimately theological “other” of reason.